An interim report on the investigator-initiated phase 2 study of pembrolizumab immunological response evaluation (INSPIRE). Issue 1 (13th March 2019) - Clouthier, Derek L.; Lien, Scott C.; Yang, S. Y. Cindy; Nguyen, Linh T.; Manem, Venkata S. K.; Gray, Diana; Ryczko, Michael; Razak, Albiruni R. A.; Lewin, Jeremy; Lheureux, Stephanie; Colombo, Ilaria; Bedard, Philippe L.; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) demonstrate unprecedented efficacy in multiple malignancies; however, the mechanisms of sensitivity and resistance are poorly understood and predictive biomarkers are scarce. INSPIRE is a phase 2 basket study to evaluate the genomic and immune landscapes of peripheral blood and tumors following pembrolizumab treatment. Methods: Patients with incurable, locally advanced or metastatic solid tumors that have progressed on standard therapy, or for whom no standard therapy exists or standard therapy was not deemed appropriate, received 200 mg pembrolizumab intravenously every three weeks. Blood and tissue samples were collected at baseline, during treatment, and at progression. One core biopsy was used for immunohistochemistry and the remaining cores were pooled and divided for genomic and immune analyses. Univariable analysis of clinical, genomic, and immunophenotyping parameters was conducted to evaluate associations with treatment response in this exploratory analysis. Results: Eighty patients were enrolled from March 21, 2016 to June 1, 2017, and 129 tumor and 382 blood samples were collected. Immune biomarkers were significantly different between the blood and tissue. T cell PD-1 was blocked (≥98%) in the blood of all patients by the third week of treatment. In the tumor, 5/11 (45%) and 11/14 (79%) patients had T cell surface PD-1 occupance at weeks six and nine, respectively. The proportion of genome copy number alterations and abundance of intratumoral 4-1BB+ PD-1+ CD8 T cells at baseline ( P  < 0.05), and fold-expansion of intratumoral CD8 T cells from baseline to cycle 2–3 ( P  < 0.05) were associated with treatment response. Conclusion: This study provides technical feasibility data for correlative studies. Tissue biopsies provide distinct data from the blood and may predict response to pembrolizumab.